Chamfer-Type Capillary Stop Valve and Its Microfluidic Application to Blood Typing Tests. (April 2019) - Chang, Yaw-Jen; Lin, Yu-Te; Liao, Chuan-Chieh
This paper presents a novel design of a capillary stop valve with a chamfered side that can be used as a flow regulator to hold an injected microfluid in the valve position in a capillary force-driven microfluidic device. Biochemical analysis can be conducted if the chamfer-type valves are placed at strategic positions according to the test protocol. Hence, the stored reagent can be dragged out of the valve for further reaction when the specimen passes through. However, countercurrent phenomena were observed in the commonly used T-type capillary stop valve (without the chamfered side). In blood typing tests, the countercurrent led to incomplete dragging and the fluid stopped flowing at the complicated mixing channel; thus, the blood typing reaction was attenuated. On the contrary, the chamfer-type valve reduced the countercurrent phenomena and ameliorated the blood typing reaction. Consequently, agglutination results can be easily discriminated from nonagglutination cases.